"synthesis of 1-(4-Chlorophenethyl)-3,6-diazahomoadamantane-9-one and Its Substituted Derivatives" (Journal of the College of Basic Education, 2025)
1-(4-chlorophenethyl)-3,6-diazahomoadamantane-9-one was synthesized through the condensation reaction of 5-(4-chlorophenyl)pentane-2-one with diethylene tetra methylene tetra amine (TATD). The C9 bridging atom in this compound and its derivatives have functional groups. were further synthesized via reactions at the carbonyl group of 1-(4-chlorophenethyl)-3,6-diazatricyclo[4.3.1.13,8]undecan-9-one. These derivatives expand the chemical diversity of the parent structure, introducing various functional modifications at the bridging position.